Study of Milkability and Its Relation With Milk Yield and Somatic Cell in Mediterranean Italian Water Buffalo - Boselli, Carlo; De Marchi, Massimo; Costa, Angela; Borghese, Antonio (Frontiers in Veterinary Science, 2020)
The milkability is defined as the ability of an animal to give a regular, complete and rapid milk secretion by the mammary gland in response to a proper milking technique. The aim of the present study was to investigated the effect of different patterns of milkability traits on milk yield and somatic cell count. Milk yield and milkability can be observed through the milk flow profiles recorded by the electronic milkmeter (Lactocorder®). A total of 2,288 milk flow curves of Mediterranean Italian buffaloes were used for one-way analysis of variance and 8 milk emission patterns were studied. The most represented milk flow curve was the type 3 (27.32%), followed by type 6 (17.79%) characterized by a very long plateau phase while the less represented curve was type 1 (4.41%) characterized by long lag time and low peak flow rate. According to analysis of variance, milk yield ranged from 2.21 to 5.22 kg per milking for type 1 and 6, respectively, while the peak flow rate was minimum (0.50 kg/min) and maximum (1.73 kg/min) for type 1 and 4, respectively. The overall total milking time was 11.29±3.68 min; lag time and milk emission time averaged 2.19±2.34 min and 4.30±2.33 min, respectively. The 12.5% (n= 286) of total curves were classified as bimodal and 60 of these were found in type 4. Based on literature, type 4 curves are representative of very short teat canals and very high milk flow. Average somatic cell score was 3.63±1.67 units, with maximum least squares mean found for type 1 and minimum for type 6. Buffaloes showing curves of type 5 and 6 were characterized by the greatest milk yield (per milking), lowest somatic cell score and lowest milking time. Results of the present study evidenced that such traits could be used in the Mediterranean buffalo as indicators to improve udder health, milkability and morphology of mammary gland.